A Portal to Dutch Academic Heritage: www.academischecollecties.nl - Reerink, Henriette (Studium, 2013)
The UNICUM development project, commissioned by the Dutch Academic Heritage Foundation Stichting Academisch Erfgoed (SAE), has been carried out by the five classic Dutch universities in 2010– 2012. UNICUM, short for ‘University Collections and University Museums’, has received a national government grant to create a digital portal to Dutch academic heritage. The portal, which can be reached via www.academischecollecties.nl, presents both academic archives and museum and library collections. Images, collection metadata and items can be found on one site. The UNICUM idea is inspired by the Online Archive of California. The project is important because it crosses the traditional sector boundaries between museums, libraries and archives, it creates awareness of the opportunities which this cross-sectoral approach offers, and it retains the context of – and the relation between – objects within collections as a whole. Moreover, the joint effort brings to light the importance of creating metadata according to international standards to stimulate re-use and exchange of content. In addition, UNICUM intended to be a technical project in which multi-level descriptions are presented and can be browsed in a structured way (collections linked to objects, and archives linked to separate documents). Now the project is finished, the focus will shift to generating content.